Comparative study on triphenylamine-based bi-armed and four-armed small molecule donors for solution processed organic solar cells. (February 2015) - Zhen, Hongyu; Peng, Zuosheng; Hou, Lintao; Jia, Tao; Li, Qi; Hou, Qiong
Abstract: A novel four-armed triphenylamine (TPA)-based molecule named (TPATh)4 TPA2 B with 4, 7-bis(4-diphenylaminophenyl)-2, 1, 3-benzothiadiazole unit as the central building block and triphenylamine-3-dodecylthiophene unit as the arms and a bi-armed TPA-based molecule named (TPATh)2 (MTPA)2 B with the same central building block and arms as those of (TPATh)4 TPA2 B were designed and synthesized by Pd-catalyzed Stille reaction. The thermal stability, photophysical and electrochemical properties of these small molecules are studied. Moreover, they are evaluated in solution processed bulk-heterojunction organic solar cells (OSCs). The device performances of the OSCs based on these small molecule donors and [6, 6]-phenyl-C71 -butyric acid methyl ester (PC71 BM) were studied. With the same core, the four-armed molecule has the higher absorption and better miscibility with PC71 BM than that of bi-armed molecule, while the bi-armed molecule (TPATh)2 (MTPA)2 B has the higher hole mobility. The power conversion efficiency of the OSCs based on (TPATh)4 TPA2 B as donor and PC71 BM as acceptor is 1.3% with open-circuit voltage 0.71 V. Highlights: A four-armed TPA-based molecule with a line molecule as core was synthesized. A bi-armed TPA-based molecule with the same core was also studied. The four-armed molecule presents better miscibility with PCBM. The OSCs based on the four-armed molecule donor show better device performances.